The Economics of Roscas and Intrahousehold Resource Allocation - Anderson, S.; Baland, J.-M. (Quarterly Journal of Economics, 2002)
This paper investigates individual motives to participate in rotating savings and credit associations (roscas). Detailed evidence from roscas in a Kenyan slum (Nairobi) suggests that most roscas are predominantly composed of women, particularly those living in a couple and earning an independent income. We propose an explanation of this based on conflictual interactions within the household. Participation in a rosea is a strategy a wife employs to protect her savings against claims by her husband for immediate consumption. The empirical implications of the model are then tested using the data collected in Kenya.